The lived experience of patients on mechanical ventilation - Portia J Jordan; Dalena van Rooyen; Johanita Strümpher (AOSIS, 2002)
Patients connected to a mechanical ventilator have to endure various experiences and emotions, which are unique to each patient. Opsomming Pasiënte wat aan 'n meganiese ventilator gekoppel is, moet verskeie emosies en ervarings deurmaak, wat aan elke persoon uniek is. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.